Accountability and global governance: The view from paternalism. Issue 2 (22nd April 2015) - Barnett, Michael
Abstract: A standard view is that global governance institutions require strong accountability mechanisms to perform effectively and legitimately. Yet these institutions are much better at preaching than practicing accountability. A standard explanation for this gap references interests. For various reasons, institutions and their creators would rather be less than more accountable, and they are quite content to live with the hypocrisy. This article points to an alternative possibility: the public interest. An article of faith is that modern governance should be staffed by relatively autonomous experts who use their specialized knowledge for the greater good; accordingly, they cannot be accountable to those who are affected by their decisions. Too much democracy, therefore, can be a source of dysfunction. Yet expert authority's virtues also can become vices; namely, insulation from those affected by their decisions can also be a source of dysfunction, most closely associated with the "iron cage." Although the possibility that expertise is both a virtue (effectiveness) and a vice (dysfunction) is well known in the literature on domestic governance, it has been neglected in discussions of global governance. Indeed, the dangers of, and dysfunctions associated with the iron cage might be greater in global governance than in domestic governance precisely because of the absence of institutional checks that often are produced by a preexisting social contract between the rulers and the ruled. I probe this possibility in the area of humanitarian governance.